Predictors of early treatment discontinuation and severe anemia in a Brazilian cohort of hepatitis C patients treated with first-generation protease inhibitors - Miotto,N. (2016)
The aim of this study was to determine risk factors for adverse events (AE)-related treatment discontinuation and severe anemia among patients with chronic hepatitis C virus (HCV) genotype 1 infection, treated with first-generation protease inhibitor (PI)-based therapy. We included all patients who initiated treatment with PI-based therapy at a Brazilian university hospital between November 2013 and December 2014. We prospectively collected data from medical records using standardized questionnaires and used Epi Info 6.0 for analysis. Severe anemia was defined as hemoglobin ≤8.5 mg/dL. We included 203 patients: 132 treated with telaprevir (TVR) and 71 treated with boceprevir (BOC). AE-related treatment discontinuation rate was 19.2% and anemia was the main reason (38.5%). Risk factors for treatment discontinuation were higher comorbidity index (OR=1.85, CI=1.05-3.25) for BOC, and higher bilirubin count (OR=1.02, CI=1.01-1.04) and lower BMI (OR=0.98, CI=0.96-0.99) for TVR. Severe anemia occurred in 35 (17.2%) patients. Risk factors for this outcome were lower estimated glomerular filtration rate (eGFR; OR=0.95, CI=0.91-0.98) for patients treated with TVR, and higher comorbidity index (OR=2.21, CI=1.04-4.67) and ribavirin dosage (OR=0.84, CI=0.72-0.99) for those treated with BOC. Fifty-five (57.3%) patients treated with TVR and 15 (27.3%) patients treated with BOC achieved sustained virological response (SVR). Among patients who received TVR and interrupted treatment due to AE (n=19), only 26.3% (n=5) achieved SVR (P=0.003). Higher number of comorbidities, lower eGFR and advanced liver disease are associated with severe anemia and early treatment cessation, which may compromise SVR achievement.